Neuroprotective effects of Dendropanax morbifera leaves on glutamate-induced oxidative cell death in HT22 mouse hippocampal neuronal cells - Park, Hye Jin; Kwak, Myounghai; Baek, Seung Hoon (Journal of Ethnopharmacology, 2020)
Ethnopharmacological relevance: Dendropanax morbifera (DM) has long been used as a traditional herbal medicine for migraines. Glutamate toxicity and oxidative stress have emerged as the possible triggers implicated in migraine pathogenesis. Aim of the study: We aimed to examine the neuroprotective effects of DM leaves (DML) on glutamate-induced oxidative cell death in HT22 mouse hippocampal neuronal cells. Materials and methods: Molecular authentication of DML was assessed using DNA barcoding analysis. Four different solvent extracts of DML were prepared and subjected to antioxidant activity and phytochemical assays. Neuroprotective effects of DML extracts were evaluated using relevant biochemical and imaging assays that measure cell viability/death, ROS generation, Ca2+ levels, mitochondrial dysfunction, and AIF nuclear translocation. Results: The sequences of matK, rbcL, atpF-H, and psbK-I in DML were identical with those in voucher specimens, confirming that DML was indeed D. morbifera. The ethyl acetate extract of DML (DMLE) showed the highest flavonoid and phenolic content, and prominent DPPH/superoxide radical scavenging and reducing power activities. In the HT22 cell model, glutamate was shown to be the causative agent for apoptotic cell death via elevation of intracellular ROS and Ca2+ levels, induction of mitochondrial depolarization and membrane permeabilization, and translocation of AIF to the nucleus. Of note, N-acetyl-L-cysteine and necrostatin-1, but not z-VAD-fmk, completely prevented glutamate-induced cell death, implying that oxidative stress and AIF translocation were pivotal in glutamate cytotoxicity. DMLE significantly recovered glutamate-induced apoptotic cell death in a concentration-dependent manner. It completely inhibited intracellular/mitochondrial ROS generation, the elevation of Ca2+ levels, and mitochondrial dysfunction induced by glutamate during early exposure within 8 h. It significantly reversed subsequent AIF nuclear translocation after 12 h of treatment. Antioxidant activities of DMLE may be the protective mechanism that regulates homeostatic balance of ROS and Ca2+ as well as maintains mitochondrial function. Conclusions: DMLE shows significant neuroprotective effects against glutamate-induced oxidative neuronal cell death. Therefore, DM could be a potential therapeutic candidate for neurological disorders propagated by glutamate toxicity.
Keywords: Animals; Araliaceae; Biphenyl Compounds; Cell Death; Cell Line; Glutamic Acid; Hippocampus; Mice; Mitochondria; Neurons; Neuroprotective Agents; Oxidative Stress; Picrates; Plant Extracts; Plant Leaves; Reactive Oxygen Species; Superoxides; AIF; Dendropanax morbifera; Glutamate oxidative toxicity; HT22; Neuroprotection